Father Involvement, Drinking to Cope, Coping Strategies, and Perceived Stress: A Correlational Study of University Students in Jakarta - Hifizah Nur; Dian Misrawati (Tazkiya Journal of Psychology, 2025)
The high levels of stress and the use of maladaptive coping mechanisms, including alcohol consumption among students, indicate the need for efforts to understand protective factors that can strengthen psychological resilience. One factor that potentially plays a significant role is father involvement in young adult life. This study aims to explore the relationship between father involvement and three indicators of student mental health: perceived stress levels, adaptive coping strategies, and maladaptive coping through alcohol consumption. This research uses a quantitative approach with an exploratory correlational design. A total of 267 college students in Jakarta participated as respondents by filling out a self-report questionnaire. The measurement tools used in this study are the Father Involvement Scale, the Perceived Stress Scale (PSS), the Coping Stress Scale, and the Drinking Motive Questionnaire-Revised (DMQR). The analysis was conducted to identify patterns of relationships between variables without assuming a cause-and-effect relationship. The research findings indicate that father involvement is negatively correlated with stress levels and coping through alcohol consumption and positively correlated with adaptive coping strategies. Moreover, elevated stress levels correlate positively with the utilisation of alcohol as a coping strategy. This finding confirms that fatherly involvement plays an important role as a protective factor against stress and maladaptive coping behaviours in college students. As an exploratory study, these results provide a foundation for further research to test a deeper causal model related to the role of family support on students' mental health.